(untitled) (Research, Society and Development, 2022)
Dental bleaching can be considered a viable and conservative, minimally invasive option that generates satisfactory results when there are color changes. This case report is a study on bleaching vital teeth, describing the step-by-step procedure performed, in which different approaches are associated with existing teeth whitening techniques and the necessary care and improvement of the saturation of teeth to long term. The objective of this work is to monitor and record the tooth whitening process of a patient with saturated teeth. A bibliographical survey was carried out in the PubMed, BVS and SciElo databases, selecting articles in Portuguese and English from the last 10 years with the keywords mentioned below. The work was submitted and approved by CEP under CAAE 59272822.1.0000.5549 and protocol 5.526.765. Patient was selected according to the degree of tooth saturation. After signing the free and informed consent form, desensitization treatment was performed on the teeth, followed by bleaching techniques on vital teeth, the homemade technique being recommended, which consists of nocturnal application of 22% carbamide peroxide, associated with applications of peroxide in the office. of hydrogen 35%. It is possible to observe that the mixed technique is effective and safe, following the manufacturers’ recommendations at all stages and that it provided a change in the saturation of the teeth, generating positive results. Both techniques require knowledge and care, being clinically indicated to achieve the best results for the patient’s treatment.